Cancer Risk in Pediatric-Onset Inflammatory Bowel Disease - El-Matary, Wael; Bernstein, Charles N. (Frontiers in Pediatrics, 2020)
Inflammatory bowel disease (IBD) is a chronic, immune-mediated, non-curable disease. The incidence of IBD appears to have risen over the last few decades especially in the pediatric age group. IBD usually presents with gastrointestinal symptoms, including abdominal pain, diarrhea, and bleeding per rectum but can also be associated with systemic symptoms such as weight loss, fatigue, joint and skin problems, and psychological comorbidities. One major complication is gastrointestinal and extra-intestinal malignancy. This review discusses literature that focuses on cancer risk of pediatric-onset IBD.